THE EFFECT OF FLEXIBILITY EXERCISE ON FATIGUE SCORE AND BLOOD PRESSURE IN HEMODIALYSIS PATIENTS AT HOSPITAL X, SERANG DISTRICT - Esterlise Nainggolan, Marischa Wanti; Widani, Ni Luh; Supardi, Sudibyo (Nursing Current: Jurnal Keperawatan, 2025)
Chronic kidney failure is becoming increasingly common and rising annually. Patients in stage five require hemodialysis or kidney transplantation due to the risk of blood pressure instability and fatigue. This study aimed to analyze the effect of flexibility exercise on reducing fatigue scores and blood pressure in hemodialysis patients at "X" Hospital, Serang Regency. A quasi-experimental pretest-posttest design was conducted from August to September 2024, involving 28 participants in the intervention group and 28 in the control group. The participants were selected using purposive sampling to ensure they met specific inclusion criteria relevant to the study. The intervention lasted for four weeks, utilizing the Fatigue Severity Scale (FSS) questionnaire and blood pressure measurements as research instruments. At baseline, most participants in both groups had severe fatigue (intervention: 85.7%; control: 92.9%) and hypertension (systolic: severe in 78.6% vs. 82.1%; diastolic: mild in 100% vs. 96.4%). Post-intervention, the exercise group showed significant reductions in fatigue (p=0.001) and systolic blood pressure (p=0.001), but not in diastolic blood pressure (p=0.599). The control group showeed no significant changes (fatigue: p=0.117; systolic: p=0.085; diastolic: p=0.225). Logistic regression indicated that flexibility exercise, occupation, and dialysis duration significantly influenced reductions in fatigue and systolic pressure (p<0.05), while gender and education did not (p>0.05). The intervention reduced fatigue by 71% (OR: 9.954; p=0.016) and systolic hypertension likelihood by 4-fold (p=0.003) compared to controls. The flexibility exercise intervention resulted in a 71% reduction in fatigue (OR = 9.954; p = 0.016) and significantly increased the likelihood of systolic blood pressure improvement by a factor of four compared to the control group (OR = 4.012; p = 0.003). Flexibility exercise is thus effective in reducing fatigue and blood pressure in hemodialysis patients. Further research is recommended to investigate external factors, such as social support, psychological conditions, and lifestyle influences to better understand the health outcomes of hemodialysis patients.